Analisis Keausan Saw Blade Akibat Variasi Kecepatan Pemajuan Pada Mesin Cold Saw di PT Krakatau Baja Konstruksi - Tamam, Sahrul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to evaluate the effect of feed rate (advance speed) on the wear of Creusabro 4800 saw blades during the cutting of low-carbon steel using a cold saw machine with a constant cutting speed of 107 m/s. The methods employed include literature review, direct field observation, interviews with technicians and operators, and data analysis from operational logbooks over a 40-day period. The results show that increasing the advance speed significantly accelerates tooth wear, reduces the number of cuts that can be performed, and affects the quality of the cut surface. An advance speed of 0.05 m/s produced 1200 cuts with 0.20 mm wear, while at 0.40 m/s, wear increased to 1.00 mm and the number of cuts dropped sharply to 300 units. Observed wear patterns included flank wear, rounding, and chipping, which were aggravated by thermal load and cyclic pressure due to the geometry of materials such as H-beams and C-channels. The optimal advance speed range was found between 0.10–0.20 m/s, where the number of cuts remained high and wear was within acceptable limits. This study recommends implementing a blade replacement logbook system, using active cooling systems, and evaluating the use of TCT blades as an alternative to improve cutting efficiency and tool life in industrial production settings